The Effect of Home Architecture on Child Rearing - Seyedian, Seyed Ali; Ghorbani, Fahime (Civil Engineering Journal, 2016)
Human beings always live in embedded place called home where is one of the main places influence them. Since home has mental relationship with family, its architecture is severely important and undeniable. It is established that training occur in every periods of life and childhood has the most significant role comparable to other periods. On the other hand, the concept of home is widely used in child welfare policies and practises, we do, however, recognize that children’s social relations and belonging to the place called ’home’ are fluid, contextual and mobile. Moreover, the quality of growing place of children is the basic for maturity and training, so the role of architecture becomes more worthy. In the current work with focus on the role of home architecture on the children’s training, different parameters were studied. In addition, the role of architecture in some characters of children such as creativity, mobility, identity and etc is the important effect of this art on the children’s training which attracted little attention since now. This study, using descriptive and analytical methods, enumerates some of the needs of the child, The capacities of architecture in the direction of training, in the other word, the role and effect of architecture of living place on parenting and the formation of their personalities and finally by providing appropriate solutions architecture, such as educational workshop spaces, spaces with high security, both physically and mentally and to improve parenting are discussed.